2011
DOI: 10.1177/0093854811420678
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Demonstration of Training Probation Officers in Evidence-Based Community Supervision

Abstract: The present study evaluated a training program for probation officers based on the risk-need-responsivity (RNR) model of offender rehabilitation. A total of 80 officers were randomly assigned to either training or a no training condition. The probation officers then recruited 143 probationers and audiotaped their sessions at the beginning of supervision, 3 months later, and 6 months later. The audiotapes were coded with respect to the officers’ adherence to the RNR model. The experimental probation officers de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
204
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(210 citation statements)
references
References 26 publications
2
204
0
3
Order By: Relevance
“…The strategic training initiative in community supervision model (STICS; Bonta et al, 2011) specifically aims to address the need for prioritization and strategic case management that was also raised by respondents who were challenged by clients with multiple moderate-to high-risk need areas. The STICS action plan not only recognizes the interrelationship between needs but also the hierarchy of needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategic training initiative in community supervision model (STICS; Bonta et al, 2011) specifically aims to address the need for prioritization and strategic case management that was also raised by respondents who were challenged by clients with multiple moderate-to high-risk need areas. The STICS action plan not only recognizes the interrelationship between needs but also the hierarchy of needs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized control study, Bonta and colleagues (2011) demonstrated that training probation officers to be more focused on criminogenic needs (procriminal attitudes in particular) was effective in reducing the likelihood of reoffending. Clients supervised by officers who received such training and support had a two year recidivism rate of 25.3% while clients supervised by the control group officers had a recidivism rate of 41.5% (Bonta et al, 2011). To that end, there have been calls within the RNR field for a change in the role of probation officers from that of "case managers/resource brokers" (i.e., making referrals based on assessment) to "change agents" (Bourgon, Gutierrez, & Ashton, 2011).…”
Section: Research On Implementationmentioning
confidence: 99%
“…It seems, however, that the probation officers' match between the assessed risks and needs and the intervention plans must be improved. Providing training and/or coaching to probation officers may help improve this match, and this strategy has been effective in Canadian practice (Bonta et al 2011). In health care, introducing a (computerized) decision-based support system has improved practitioners' performance (Garg et al 2005).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Rather than assume that these appointments are too brief to matter, research now indicates that offi cers can use these interactions to be change agents and reduce recidivism (Kennealy et al 2012 ;Manchak et al 2014 ;Raynor et al 2014 ;Raynor and Vanstone 2015 ). In fact, programs have been developed that have successfully trained supervising offi cers to use offi ce visits for therapeutic purposes (Andrews and Bonta 2010 ;Bonta et al 2011 ;Lowenkamp et al 2014 ;Robinson et al 2012 ;Smith et al 2012 ).…”
Section: Recommendation 7: Teach Prison Offi Cers To Be Change Agentsmentioning
confidence: 99%